2014
DOI: 10.1007/s10661-014-3875-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of polyethylene by Trichoderma harzianum—SEM, FTIR, and NMR analyses

Abstract: Trichoderma harzianum was isolated from local dumpsites of Shivamogga District for use in the biodegradation of polyethylene. Soil sample of that dumpsite was used for isolation of T. harzianum. Degradation was carried out using autoclaved, UV-treated, and surface-sterilized polyethylene. Degradation was monitored by observing weight loss and changes in physical structure by scanning electron microscopy, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. T. harzianum was able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 17 publications
1
22
0
5
Order By: Relevance
“…UV light is an initiator of PE oxidation; it produces carbonyl groups that are the main factors for the beginning of biodegradation, promoting the microorganisms' attack on the shorter segments of PE molecular chains. One example is strain Trichoderma harzianum that efficiently degraded PE treated with UV radiation, causing the formation of cavities and erosion on the plastic surface, as well as the formation of new chemical groups, detected by FTIR and NMR (Sowmya et al, 2014). On the other hand, exposing films to the sunlight as pretreatment is not enough to promote biodegradation, but this method is important to increase strains growth on the polymers, as the case of Pleurotus ostreatus.…”
Section: Fungimentioning
confidence: 99%
“…UV light is an initiator of PE oxidation; it produces carbonyl groups that are the main factors for the beginning of biodegradation, promoting the microorganisms' attack on the shorter segments of PE molecular chains. One example is strain Trichoderma harzianum that efficiently degraded PE treated with UV radiation, causing the formation of cavities and erosion on the plastic surface, as well as the formation of new chemical groups, detected by FTIR and NMR (Sowmya et al, 2014). On the other hand, exposing films to the sunlight as pretreatment is not enough to promote biodegradation, but this method is important to increase strains growth on the polymers, as the case of Pleurotus ostreatus.…”
Section: Fungimentioning
confidence: 99%
“…According to [33], the production of this enzyme increases when the microbes are in close proximity with the polyethene. Reference [34] was able to extract the crude laccase enzyme which was incubated with polyethene and led to degradation as was evidenced through weight loss, FTIR, and SEM. Esterases catalyze the cleavage of ester bonds [35] of short-chain triglycerides or esters.…”
Section: Resultsmentioning
confidence: 99%
“…PE can be degraded through molecular mechanisms such as chemical, thermal, photo and biodegradation [22] , [67] , [72] . With regards to its biodegradation, it has been reported that it can be effectively degraded by several bacterial species through the use of enzymes such as amylase, laccase, LiP and MnP.…”
Section: Applications Of Peroxidases In Industry Set Upmentioning
confidence: 99%